Smartphone Use as a Driver of Social Behavior Changes in Daily Life - Robitotul Islamiah; Dedy Dwi Putra; Linda Maulidiah (Education and Sociedad Journal, 2024)
This study aims to identify the impact of smartphone use on students' social behavior. This study was driven by the phenomenon of increasing smartphone use among teenagers that affects the way they interact, both in cyberspace and in face-to-face communication. The method used in this study is a qualitative approach with a case study type. Data were collected through interview techniques, observations, and documentation from students, teachers, and school staff. Data analysis was carried out using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and drawing conclusions. The findings show that although smartphones help students maintain long-distance relationships and expand social networks, excessive use also causes a decrease in face-to-face interactions, which impacts their social skills, such as direct communication and empathy. The limitations of this study lie in the limited scope of only one school, so the results cannot be generalized to the entire population. The contribution of this study provides insight into how smartphones change students' social communication patterns and provides recommendations for education regarding the wise use of technology. This study also opens up opportunities for further studies on the impact of smartphone use on adolescent mental health and their social development.